Development of Electronic Student Worksheet Based on Guided Inquiry on The Topic of Photosynthesis - Aditya Fahlevi; Jumadi Jumadi; Arina Novia Dewi; Feby Permata Sari (Postgraduate, University of Mataram, 2022)
This study is a form of research and development through implementing a Four-D model to generate electronic student worksheets based on guided inquiry on the topic of photosynthesis. The purpose of this research is to attain electronic student worksheets that can be worth using in science learning. Product quality is assessed based on the feasibility and response of learners to the practicality of use. The instruments used in the study were electronic student worksheet eligibility assessment sheets and student response assessment sheets developed using the Likert scale.Â The results showed that the characteristics of electronic student worksheets based on guided inquiry consist of steps for problem identification, hypothesis definition, problem formulation, data collection, verification of results, and generalization to conclusion drawing. another finding was that electronic student worksheets based on guided inquiry on the topic of photosynthesis obtained a Feasibility score with an average of 108.20 with excellent categories and the results of the student response test obtained a score of 91.80 with an excellent category